2022
DOI: 10.1038/s41598-022-12569-8
|View full text |Cite
|
Sign up to set email alerts
|

Explaining sex differences in risk of bloodstream infections using mediation analysis in the population-based HUNT study in Norway

Abstract: Previous studies indicate sex differences in incidence and severity of bloodstream infections (BSI). We examined the effect of sex on risk of BSI, BSI mortality, and BSI caused by the most common infecting bacteria. Using causal mediation analyses, we assessed if this effect is mediated by health behaviours (smoking, alcohol consumption), education, cardiovascular risk factors (systolic blood pressure, non-HDL cholesterol, body mass index) and selected comorbidities. This prospective study included 64,040 part… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…In a study examining nutritional status in European populations, there were indications of low iron status linked to higher mortality from COVID-19 18 . There is evidence of sex differences in incidence and outcomes of COVID-19 infection 19 21 . Few studies have evaluated sex differences in iron status at time of infection.…”
Section: Introductionmentioning
confidence: 99%
“…In a study examining nutritional status in European populations, there were indications of low iron status linked to higher mortality from COVID-19 18 . There is evidence of sex differences in incidence and outcomes of COVID-19 infection 19 21 . Few studies have evaluated sex differences in iron status at time of infection.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with patients without comorbidities, the duration of recovery from community-acquired infections is longer for those with immunosuppression, cancer and chronic respiratory diseases [ 36 , 51 ]. Previous studies have shown that differences in health and lifestyle among men and women in combination with CAI can lead to longer hospital stays [ 52 , 53 ]. In addition, it has been reported that in males, infections are at a more advanced stage when they are admitted to hospital, further increasing the length of hospitalization [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Men also display heart disease at a younger age than women [ 87 ]. In one prospective cohort which included 64,040 participants, the risk of bloodstream infection was reported to be 41% higher among men than among women and one-third of this excess risk was mediated by cardiovascular risk factors and comorbidities [ 89 ].…”
Section: Clinical Studiesmentioning
confidence: 99%